Empirical model for estimation of global solar radiation at lowland region Biratnagar using satellite data - Shrestha, Ganesh Kumar; Pandey, Binod; Joshi, Usha; Poudyal, Khem N. (BIBECHANA, 2021)
This study proposes to find the regression coefficient of the modified Angstrom type model for the estimation of global solar radiation (GSR) in lowland Biratnagar (Lat. 26.5º N, Long. 87.3º E and Alt. 72m) using relative sunshine duration and satellite data of GSR. Using the regression technique, the empirical constants 0.29 and 0.56 are found in the modified Angstrom model. Furthermore, the Modified Angstrom model along with other linear models such as Glover and McCulloch model, Page model, Rietveld model, and Turton’s model are statistically assessed to evaluate the significance of models. Statistical tests like MPE, MBE, RMSE, and CC reveal that all these models are statistically significant. These findings can be utilized for other locations with a high confidence level at the similar climatic locations of Nepal. BIBECHANA 18 (1) (2021) 193-200